Selenium supplementation in thyroid eye disease: an updated review from a clinical ophthalmic perspective - Foos, William; Maliakkal Hernandez, Janice; Mansour, Tamer N (Orbit (Amsterdam), 2024)
Thyroid eye disease (TED) consists of a spectrum of autoimmune orbital pathology that threatens patients' quality of life and vision. Research suggests that oxidative stress plays a role in both the thyroid gland and orbit. Selenium has been proposed as a potential therapeutic adjunct given its role in thyroid physiology and antioxidant metabolism. Furthermore, selenium status has been linked to multiple pathological thyroid states. Despite the preponderance of evidence demonstrating a role for selenium in thyroid disease, limited research exists highlighting its role in TED specifically. This review summarizes the pathophysiology and role of selenium in thyroid eye disease (TED) and the current body of evidence including in vitro and in vivo studies highlighting the role for supplementation in clinical ophthalmic practice. Notably, relatively lower selenium levels have been shown to have a modest correlation with severity of thyroid eye disease. Selenium supplementation has shown some benefit in patients with mild Graves' Orbitopathy in European populations presumed deficient. Despite the preponderance of evidence demonstrating a role for selenium in thyroid disease, limited data is available to conclusively expand its role in TED outside of a 6-month course of supplementation in selenium deficient or relatively deficient populations. Data subject to geographic and population differences in selenium levels limits the generalizability of supplementation in TED. Despite mechanistic evidence of its antioxidant effects in TED beyond the advantages of thyroid disease in general, the benefits of selenium supplementation should be interrogated further and contextually tailored in both clinical and research formats for ophthalmic practice.